DESIGN CONSIDERATIONS FOR TRAWL WINCHES - VELU, M (Fishery Technology, 2016)
For efficient functioning of a trawl winch it is essential thm all component parts should be designed carefully taking into consideration all the relevant factors such as quantum and type of load each component is subjected to, amount of maintenance it will receive during actutal operation, type of driv.:: for the winch etc. Based on the practices adopted at the Central Institute Of Fisheries Technology certain guide lines are proposed in this p::tper for designing of trawl winches.